The prognosis and adjuvant chemotherapy in KRAS mutation patients with stage I lung adenocarcinoma - Shangshang Ma; Kun Li; Rangrang Wang; Jiayi Qian; Yongfei Fan; Xichun Qin; Mingjun Li; Leilei Wu (Clinical Surgical Oncology)
Background: Adjuvant chemotherapy (ACT) remains the current first-line systemic treatment option for patients with KRAS-mutated lung adenocarcinoma (LUAD), but the response is not effective. The prognosis of ACT in patients with KRAS mutations in stage I LUAD has not yet been effectively explored. Methods: Detailed data about patients with stage I LUAD from Shanghai Pulmonary Hospital were collected in this ambispective study. Pearson's Chi-square test, Kaplan-Meier analysis, and Cox proportional hazard models were performed in this study. The primary observational endpoint was overall survival (OS). Sensitivity analysis was performed to assess the robustness of the findings. Results: In this study population, 10.87% (194 out of 1783) of stage I LUAD patients possessed KRAS mutations. In the KRAS-mutated cohort, 7 patients harbored EGFR L858R point mutation, 2 patients exhibited EGFR exon 19 Del mutation, 2 patients had ALK rearrangement, and 1 patient for other EGFR mutations. Patients harboring KRAS mutations had a worse OS compared to KRAS wild-type (WT) patients (5-year OS rate: 96% vs. 82%, P ​< ​0.001). In addition, the KARS(G12C) mutation was an independent factor for poor prognosis (P ​< ​0.001). Importantly, ACT improved survival in patients with stage IB LUAD (P ​= ​0.02) while not improved survival in the group of stage IB patients with KRAS mutations (P ​= ​0.31). Conclusions: KRAS mutation could co-occur with EGFR mutation and ALK rearrangement. KRAS mutation was associated with poor prognosis in stage I LUAD patients. In addition, ACT did not improve prognosis in stage IB LUAD patients with KRAS mutations. Our findings require more research to be confirmed.